Deportation of Central American women victims of trafficking - IZCARA-PALACIOS, Simón Pedro; ANDRADE-RUBIO, Karla Lorena (Papeles de Población; Vol. 22 Núm. 90 (2016), 2018)
The United States adult entertainment industry demand undocumented migrant women because they work more hours, receive lower wages and are preferred by customers as they are more docile than native women. In this industry as important as the recruitment of new women is the expulsion of those that are not profitable. This study, based on a qualitative methodology that includes in-depth interviews with seventy-five Central American women victims of sexual exploitation in the United States, concludes that procurers use immigration law to get rid of pregnant, older, non-profitable and conflicting women, and customers use the law to force foreign women to fulfil their whims. In conclusion, immigration law promotes human trafficking because it empowers procurers and customers, and makes victims more vulnerable.